What makes an entrepreneurship independent? Evidence from time use survey - Ari Hyytinen; Olli-Pekka Ruuskanen (The Research Institute of the Finnish Economy (ETLA), 2006)
It is a well-documented empirical regularity that it is more satisfying to be self-employed than to work as an employee for an organization. A large part of this difference in job satisfaction is in the literature attributed to the strong perception of independence by the self-employed. In this paper we study people's time use as a source of entrepreneurial independence. By making use of disaggregated sequential microdata on people's time use, we are able to document that the perceived independence hardly derives from more flexible time use: The selfemployed work longer effective hours as well as more in the evenings and weekends than the organizationally employed. Albeit being able to time one's work may be a signal of flexibility in time use, the self-employed have less pure leisure and are less frequently absent from work in general and because of sickness on weekdays in particular. Moreover, we document that the self-employed who have small children are more likely to work after 5 p.m., when the communal day-care centers close. On the basis of these findings it is not surpirising that the selfemployed perceive that they are more often than the organizationally employed under time pressure and in hurry.
Keywords: M13; J22; J28; 330; Entrepreneurship; allocation of time; job satisfaction; Entrepreneurship-Ansatz; Zeitbudgetforschung; Arbeitszufriedenheit; Finnland